Tomographic evaluation of mandibular buccal shelf in patients with different vertical growth pattern = Evaluación de la placa ósea mandibular en pacientes con diferente patrón de crecimiento vertical - García Gonzales, Luis Angel
The purpose of this research was the tomographic evaluation of the Mandibular Buccal Shelf (MBS) in orthodontic patients with different vertical growth pattern. An observational, descriptive, cross-sectional and retrospective study was conducted. Tomographic images of patients aged 14 to 40 years were observed and a database was formed with those that met the inclusion criteria. The sample size was 10 for each group according to vertical growth pattern (hypodivergent, normodivergent and hyperdivergent). Then four zones of frequent insertion of extralveolar mini-screws were selected in the MBS, taking as a reference the mesial and distal roots of the first and second mandibular molar. When comparing the characteristics of MBS between vertical growth patterns, between sexes and hemiarchs, no statistically significant differences were found. However, when the characteristics of MBS were compared according to the reference root, it was found that there were statistically significant differences. The vestibular area to the distal root of the second mandibular molar presented the highest values in terms of angulation, height and thickness. There are no significant differences in the bone characteristics of MBS according to vertical growth patterns, sexes or hemiarchs. Angulation, height and thickness progressively increase from the vestibular bone of the mesial root of the first mandibular molar to the distal root of the second molar.